Processing and electrical response of fully polymer piezoelectric filaments for e-textiles applications - Martins, R. S. (2014)
This paper describes the production and characterization of novel geometries for piezoelectric products with a large potential in the design and implementation of flexible sensors produced at low cost and high rates. In particular, the filament geometry, appropriate for integration into textiles, is analyzed. Piezoelectric filaments producing electrical signals under bending or traction stress, thus acting as mechanical sensors, have been produced and tested, and are presented in this paper.